On Asymptotically Lacunary Statistical Equivalent Set Sequences - Uğur Ulusu; Fatih Nuray (Journal of Mathematics)
This paper presents three definitions which are natural combination of the definitions of asymptotic equivalence, statistical convergence, lacunary statistical convergence, and Wijsman convergence. In addition, we also present asymptotically equivalent (Wijsman sense) analogs of theorems in Patterson and Savaş (2006).